• Math background
  • Math background
  • Mathematics background
  • Mathematics background
  • Fundamentals of Statistics
  • Math graphics free wallpaper in free desktop
  • stock vector : math background
  • Math background, discrete math
  • Free Math Background for Powerpoint Slides
  • Royalty-Free (RF) Clipart Illustration of a Math
  • Mathematica -photos of some famous historical figures
  • binary system
  • Pascals triangle.
  • Conic section
  • Welcome to mathematics
  • Taylor polynomials and Taylor series -
  • ... theory of Taylor series to show that the
  • The Unit Circle
  • Graphs of the functions sin(x) and cos(x),
  • GOne of the applications of the zeta function
  • Taylor Series Approximation Illustrated
  • Matematik eğitiminin sağlıklı
  • crazy math(12)
  • crazy math(11)
  • crazy math(10)
  • crazy math(9)
  • crazy math(8)
  • crazy math(7)
  • crazy math(6)
  • crazy math(5)
  • crazy math(4)
  • crazy math(3)
  • crazy math(2)
  • crazy math(1)
  • Mickeys ears are circles which are conic sections

اوجد العدد جـ²(أ+ب) اذا علمت ان ....

الأحد، 4 ديسمبر، 2011 التسميات:





بفرض ان أ ، ب ، جـ ثلاثة اعداد حقيقية مثنى تحقق أ² (ب+جـ) = ب² (أ+جـ) = 2009
فإن العدد جـ² (أ+ب) = ؟؟

الحل :
أ² (ب+جـ) = 2009   اذاً   أ² ب + أ² جـ = 2009                     (1)
ب² (أ+جـ) = 2009   اذاً   أ ب² + ب² جـ = 2009                    (2)

بضرب (1) فى ب  ،  وضرب (2) فى أ  فينتج لدينا نظامين، وهما

أ² ب² + أ² ب جـ = 2009 ب                  (3)
أ² ب² + أ ب² جـ = 2009 أ                    (4)

ـــــــــــــــــ بطرح (3) ، (4) ـــــــــــــــــــــــــ

أ² ب جـ - أ ب² جـ = 2009ب - 2009 أ      ومنها نحصل على

أ ب جـ ( أ - ب ) = 2009 ( ب - أ )         اى ان :

أ ب جـ ( أ - ب ) = - 2009 ( أ - ب )      بقسمة الطرفين على ( أ - ب ) فنحصل على

أ ب جـ = - 2009                                (5)

بعد ان حصلنا على معادلة (5) نقوم بجمعها مع معادلة (1)

أ² ب + أ² جـ = 2009                     (1)
أ ب جـ = - 2009                           (5)

ــــــــــــــــــ بالجمع ــــــــــــــــــــــــــــــــ

أ² ب + أ² جـ + أ ب جـ = 0      بقسمة الطرفين على أ

أب + أجـ + ب جـ = 0      اذاً  جـ (أ+ب) + أ ب = 0

ثم :    جـ (أ+ب) = - أ ب          بضرب الطرفين فى  جـ

جـ² (أ+ب) = - أ ب جـ      ولكن : أ ب جـ = - 2009         (5)

اى ان : - أ ب جـ = 2009

اذاً  :  جـ² (أ+ب) = 2009

0 التعليقات:

إرسال تعليق

 
mathematics problem solving © 2010 | تعريب وتطوير : سما بلوجر | Designed by Blogger Hacks | Blogger Template by ياعرب